(3JNQjL GdOdGdGJ GdSeYjI Ydi eGcGf aj YgO QShd Gddg Udi Gddg Ydjg hSde ef GdMQa hGdUfGFY hGdeYGedGJ GdTQYjIs - (3Ydj Hf eMeO GdNRGYis
(3ChdgG (B:s
(3GdMeO ddg GdPi Ndb GdNdb hHYO hSejJg JNQjL GdOdGdGJ GdSeYjI s
(3BNQgG (B:s
(3hcJGH GdcaGjI hGdZfGA ai CMcGe GdZfGA JCdja eMeO Hf YeQ Hf eMeO GdSHJi GdeYQha HGdOQGL ced hGdMeO ddg MeOkG cKjQkG s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B6s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs